Cities in a globalizing world : global report on human settlements 2001 (Earthscan Publications, 2001)
'The world has entered the urban millennium. Nearly half the world's people are now city dwellers and the rapid increase in urban population is expected to continue mainly in developing countries. This historic transition is being further propelled by the powerful forces of globalization. The central challenge for the international community is clear: to make both urbanization and globalization work for all people instead of leaving billions behind or on the margins ... Cities in a Globalizing World: Global Report on Human Settlements 2001 is a comprehensive review of conditions in the world's.